Emergence and formation of historical subjectivities in contemporary videogames. The case of the D-Day - Venegas Ramos, Alberto (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
American video games set in the Second World War have often recreated the so-called Operation Overlord. Sagas like Call of Duty (Treyarch, 2003-2017) or Medal of Honor (Dreamworks Interactive et alii, 1999-2012), with millions of units sold, have propelled a heroic and nationalist vision of the conflict and have shaped a historical myth, to a "mythhistory", around the fact of the past that does not correspond to the documents, oral testimonies and material culture collected, evaluated, criticized and interpreted of said operation. In this paper we intend to evaluate three basic questions about this fact, the creation of historical subjectivities, the first is the reason for the emergence of these, the second is the way in which they are presented and their relationship with contemporary society and the third, the individuality of the videogame medium for the transport and dissemination of these subjective historical discourses.